Distance learning in Brazil: some notes (Research, Society and Development, 2020)
The present work is part of the dissertation, already defended, of the master in teaching of humanities and languages (MEHL), of the Franciscan University (UFN). It is a qualitative research, of the bibliographic revision type, with the objective of drawing a general historical panorama of the different forms of development of distance learning in Brazil. For this purpose, we used works by authors who deal with the theme, such as J. R. M. Alves (1994), Maia and Mattar (2007), B. Carvalho (2014), Batista and Souza (2015) and Amarilla (2011). Methodologically, this study was divided into three parts. The first involves questions related to the concept of EAD, aiming the terms that most stand out in most of the concepts about EAD. The second part deals with the historical trajectory of this modality, focusing on its performance in Brazil. Finally, the third part presents the resources that interactive environments and informal training, through virtual means, offer. In addition, the laws referring to the research theme were consulted. It is observed that the potentials of these virtual training environments are still in the process of construction and reflection, both in relation to their contributions with the distance courses, as in the academic researches that involve the theme.